2016
DOI: 10.4300/jgme-d-15-00730.1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on the Impact of a Just-in-Time Room on Trainees and Supervising Physicians in a Pediatric Emergency Department

Abstract: Background Just-in-time (JIT) training refers to education occurring immediately prior to clinical encounters. An in situ JIT room in a pediatric emergency department (ED) was created for procedural education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…108,111,112 However, JITT may not be helpful for all types of procedures and training with some research showing conflicting success rate for certain procedures, such as pediatric intubation and infant lumbar puncture. 113,114 Importantly, in the era of mounting technology and easy availability, it is vital to screen the JITT resources for quality and applicability prior to incorporation into clinical practice. 115,116 One study performed a systematic search of YouTube TM to assess videos focused on teaching ophthalmoscopy.…”
Section: A Just-in-time Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…108,111,112 However, JITT may not be helpful for all types of procedures and training with some research showing conflicting success rate for certain procedures, such as pediatric intubation and infant lumbar puncture. 113,114 Importantly, in the era of mounting technology and easy availability, it is vital to screen the JITT resources for quality and applicability prior to incorporation into clinical practice. 115,116 One study performed a systematic search of YouTube TM to assess videos focused on teaching ophthalmoscopy.…”
Section: A Just-in-time Trainingmentioning
confidence: 99%
“… 108 , 111 , 112 However, JITT may not be helpful for all types of procedures and training with some research showing conflicting success rate for certain procedures, such as pediatric intubation and infant lumbar puncture. 113 , 114 …”
Section: Incorporating Technologymentioning
confidence: 99%
“…JIT training aims to provide relevant instruction at the point of clinical care 14 and has a demonstrated track record of success in medicine for a variety of procedures. [15][16][17][18] Among the many published studies of JIT training are patient-specific three-dimensional teaching models, in situ simulations, 19 and simulator practice prior to performance of bedside or surgical procedures. [20][21][22][23][24][25][26][27] Video is an optimal media for JIT training just prior to the actual performance of a procedure or maneuver; platforms to review video are ubiquitous in the clinical environment (desktop computers and mobile devices), and video provides a visual demonstration of the physical actions required.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] JiTT is a method of out-of-classroom foundational instruction, at times in the form of a video or simulation, aimed at bolstering clinical learning. Previous studies have reported that JiTT is an effective tool in helping physicians-in-training improve their confidence and comfort level with procedural interventions (e.g., suturing, lumbar punctures, and intraosseous needle placement), [12][13][14] while also reinforcing skills that were previously learned (e.g., splinting). 14 Clinical guidelines have long been used by clinicians as a framework (informed by evidence-based medicine) for delivering patient care and developing standards of care.…”
Section: Introductionmentioning
confidence: 99%